Assistance equipment refill filter water to meet drinking water needs in pondok Tahfidz Quran Al Fitrah - Hardi, Surya; Ginting, Elisabeth (Talenta Publisher, 2019)
Water serves to transport minerals, vitamins, proteins and other nutrients throughout the body. Body temperature balance will greatly depend on water, because water is a lubricant of the body's tissues as well as pads of joints, bones, and muscles. Once the importance of water for human survival so that the availability and sustainability of water for living things must be maintained. In the life of modern society in Indonesia today, the supply of clean water to a community is usually supplied by local government-owned water companies. But due to network limitations or production capacity, often not all communities can enjoy the clean water facilities. Islamic boarding schools are religious-based educational facilities whose management is still constrained by funding problems. So the facilities are always in a limited state. As is the case with the Quran Al-Fitrah tahfidz Islamic boarding school, which is located in Namo Rambe, which has difficulty in providing clean water to be drunk at the boarding school.